2021
DOI: 10.1002/acm2.13319
|View full text |Cite
|
Sign up to set email alerts
|

Development of a physical geometric phantom for deformable image registration credentialing of radiotherapy centers for a clinical trial

Abstract: This study aimed to develop a physical geometric phantom for the deformable image registration (DIR) credentialing of radiotherapy centers for a clinical trial and tested the feasibility of the proposed phantom at multiple domestic and international institutions. Methods and materials: The phantom reproduced tumor shrinkage, rectum shape change, and body shrinkage using several physical phantoms with custom inserts. We tested the feasibility of the proposed phantom using 5 DIR patterns at 17 domestic and 2 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Several studies have evaluated DIR accuracy using many DIR algorithm. 13,14,17,41 These studies showed that the DIR accuracy strongly depended on the DIR algorithm and procedure. Our result was consistent with their studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have evaluated DIR accuracy using many DIR algorithm. 13,14,17,41 These studies showed that the DIR accuracy strongly depended on the DIR algorithm and procedure. Our result was consistent with their studies.…”
Section: Discussionmentioning
confidence: 99%
“…The physical phantom configuration with various inserts proposed in this study is an improved version of the phantom originally developed and reported by Kadoya et al. 17 The physical size of improved phantom was same as the original phantom. The physical size of large phantom had a length, width, and height of 30, 8, and 15 cm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations